2001
DOI: 10.1038/sj.bmt.1702836
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of positive surveillance for cytomegalovirus (CMV) by PCR in allograft recipients at low risk of CMV

Abstract: Summary:Cytomegalovirus (CMV) causes significant morbidity and mortality following allogeneic haemopoietic stem cell transplantation. A pre-emptive strategy for ganciclovir therapy is widely used, whereby treatment is commenced on finding positive evidence of CMV replication. Surveillance by PCR has increased the sensitivity for CMV detection, but it is not known whether this may detect cases with evidence of CMV DNAemia who have a low probability of CMV disease. We reviewed our experience of CMV infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is notable that other, smaller studies that have employed screening for primary CMV infection among seronegative SCT recipients who receive "CMV-safe" blood product support have documented infection rates ranging from 6.7% to over 50%, depending upon whether pp65 antigenemia or polymerase chain reaction (PCR) for CMV DNA is utilized. [26][27][28] The higher sensitivity of PCR for CMV DNA may lead to lower positive predictive values for CMV disease in seronegative patients; thus, antigenemia-based surveillance may be preferable for this patient population. 26 Importantly, our results are also consistent with the results of the previously reported randomized trial that compared filtered and seronegative blood product support, where a trend toward a higher CMV indicates cytomegalovirus; CI, confidence interval; RBC, red blood cell product; PLT, platelet product; LR, leukoreduced; and NE, not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notable that other, smaller studies that have employed screening for primary CMV infection among seronegative SCT recipients who receive "CMV-safe" blood product support have documented infection rates ranging from 6.7% to over 50%, depending upon whether pp65 antigenemia or polymerase chain reaction (PCR) for CMV DNA is utilized. [26][27][28] The higher sensitivity of PCR for CMV DNA may lead to lower positive predictive values for CMV disease in seronegative patients; thus, antigenemia-based surveillance may be preferable for this patient population. 26 Importantly, our results are also consistent with the results of the previously reported randomized trial that compared filtered and seronegative blood product support, where a trend toward a higher CMV indicates cytomegalovirus; CI, confidence interval; RBC, red blood cell product; PLT, platelet product; LR, leukoreduced; and NE, not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The higher sensitivity of PCR for CMV DNA may lead to lower positive predictive values for CMV disease in seronegative patients; thus, antigenemia-based surveillance may be preferable for this patient population. 26 Importantly, our results are also consistent with the results of the previously reported randomized trial that compared filtered and seronegative blood product support, where a trend toward a higher CMV indicates cytomegalovirus; CI, confidence interval; RBC, red blood cell product; PLT, platelet product; LR, leukoreduced; and NE, not evaluated. *Blood product support covariates expressed as odds for TT-CMV for each additional blood product per 100 days of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, in low-risk allograft cases where both donors and recipients were ELISA negative (R−/D-) before transplantation, real-time PCR evidence showed HCMV contamination of the recipients after transplantation. Similarly, Butt et al reported that 55% of their low-risk (R−/D-) patients were HCMV positive after transplantation according to real-time PCR results [4].…”
Section: Discussionmentioning
confidence: 95%
“…Primary infection may cause different morbidities and even mortality in severe forms. It has a higher frequency, more clinical manifestations, and a higher recurrence rate than secondary infections [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,8 Therefore, these reports together with the results shown in the present study lead us to recommend the use of PCR using plasma in the surveillance of CMV. This method could be of more clinical relevance in terms of avoiding overtreatment than PCR using whole blood or leukocytes, which may often be too sensitive, and it may predict the development of CMV diseases more precisely.…”
mentioning
confidence: 97%